Evaluating Software Quality in a Point of Sales System in a Fast-Food Restaurant Using the McCall Model - Ramadhina Assidiq, Wahyu Fidi; Putro, Fidi Wincoko; Amri, Arni Muarifah (Jurnal Teknik Informatika (Jutif), 2025)
Software quality is an critical aspect in ensuring system performance and user satisfaction. This study evaluates the quality of the system called Sampos. is a system used by internal employees in managing fast food business operations for record transactions. manage raw material stocks and help track daily reports. The evaluation was conducted using the McCall model, which focuses on five primary quality factors: correctness, reliability, efficiency, integrity, and usability. Each factor is assessed through indicators that reflect the system's performance in that aspect. The measurement stage begins by assigning weights to each indicator based on its level of importance. Then. The quality value of each factor is calculated to get a comprehensive picture of system performance. The results of the evaluation showed that the correctness value was 56.2%, reliability 56%, Integrity 47.8%, and usability 46%, which are generally classified as "Pretty Good.". Meanwhile, the value of the efficiency factor is only 38.2%, so it is categorized as "not good." Overall, the Sampos system obtained an average score of 41% - 60%. This indicates that the system requires improvement, especially in the aspect of efficiency. This study contributes to proving that McCall's method can be used to evaluate applications built without documentation and by a single developer. Therefore, this study contributes a practical case study on the application of McCall’s Model as an effective method for identifying and quantifying quality weakness in small-scale operational systems.